2015
DOI: 10.1007/s00210-015-1127-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of flavonoids from Astragalus complanatus on breast cancer growth

Abstract: Flavonoids from Astragalus complanatus R.Br (FAC) had anticancer effects on many tumor cells. The current study was performed to evaluate the effects of FAC on human breast cell proliferation, apoptosis, and metastasis, as well as their active mechanism. Cell viability and growth were detected using the cell counting kit (CCK)-8 assay in vitro. Assay of FAC on induced breast cancer mortality was counted as survival time of nude mice after breast cell line inoculation. The effect of FAC on cell invasion was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…SYY is a Chinese herbal formula and certain components have been recognized to be effective in the treatment of cancer (27,28). Astragaloside IV controls collagen reduction in photoaging skin by improving suppression of the TGF-β/SMAD signaling pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…SYY is a Chinese herbal formula and certain components have been recognized to be effective in the treatment of cancer (27,28). Astragaloside IV controls collagen reduction in photoaging skin by improving suppression of the TGF-β/SMAD signaling pathway (29).…”
Section: Discussionmentioning
confidence: 99%
“…In nude mice inoculated with breast cancer cell line, AF prolongs the survival time, and inhibits the proliferation and metastasis of tumor cells in a dose-dependent manner [ 140 ]. AF and an isoflavone aglycone calycosin inhibit the proliferation through arresting cell cycle in the G0/G1 phase by decreasing cyclin D1 in human erythroleukemia cell line K562 [ 141 ].…”
Section: Anti-aging and Anti-aging Related Effects Of Astragalus Fmentioning
confidence: 99%
“…Purified AI contains 18 active ingredients, including pratensein 7- O -glucopyranoside, calycosin-7- O -β-D-glucoside, astragaloside I, astragalin, 4´-hyadroxysoflavone-7- O -β D-glucoside, pratensein, pterocarpane-3-glucoside, methylnissolin-3- O -glucoside, isomucronulatol, isorhamnetin, isorhamnetin-3- O -gentiobioside, medicarpin, 6˝-acetyl-calycosin-7D-glucoside, astragaloside V, astragaloside VI, astragaloside VII, astragaloside IV, and lrioresinol B 9 . Studies on the anticancer effects of astragalus and its main components have been performed, and abundant evidence has shown that astragalus and its main components inhibit cell proliferation, inhibit oxidative stress, and induce apoptosis in various cancer cells 10 , 11 , 12 . For example, astragalosides inhibit human colon cancer cell proliferation by inducing cell cycle arrest in the S and G2/M phases 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus mongholicus injection inhibits MCF-7 breast cancer cell proliferation by inducing G0/G1 and S phase arrest 14 . In addition, flavonoids from astragalus inhibit the development of breast cancer by promoting cancer cell apoptosis 12 . Astragaloside IV inhibits hepatic stellate cell activation by inhibiting oxidative stress and associated p38 MAPK activation 15 .…”
Section: Introductionmentioning
confidence: 99%